Apocalypse nerd - Bagge, Peter 1957- (Dark Horse, 2008)
Software engineer Perry and his friend Gordo are two average suburban guys who just wanted to go camping in North Cascade Mountains near Seattle--but Kim Jung Il had other plans. Now Seattle is a smoldering nuclear wasteland and Perry and Gordo are about to be put to the test in ways they have never imagined. From the mind of acclaimed artist Peter Bagge comes a post-apocalyptic tale which will have you both laughing and gasping in horror!